PEMANFAATAN PENERIMAAN BUKAN PAJAK UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DALAM PELAKSANAAN ANGGARAN PENGELUARAN DAN BELANJA NEGARA - Nasution, Rahmad Mulia Tama; Reni Ria Armayani; Hasibuan, Reni Ria Armayani (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Abstract   Problems: The use and utilization of non-tax revenues in the state budget to improve public welfare. How the utilization of non-tax state revenue is utilized to improve the welfare of society. Purpose: The purpose of this research is to find out whether non-tax revenues in the state revenue and expenditure budget are used and utilized properly to help people's social lives and improve people's welfare. To find out what sectors are assisted using non-tax state revenue funds, whether the utilization of non-tax state revenue is right on target and there are no obstacles in its management. Methodology: The research method used in this research is a qualitative approach with descriptive analysis techniques. The data collection method used is through academic sources and texts such as books, articles, journals, reports, research findings, news. Descriptive analysis is carried out on academic texts in accordance with the research theme to obtain results and findings regarding the utilization of non-tax state revenue to improve public welfare in the implementation of the state revenue and expenditure budget. Results: The utilization of Non-Tax State Revenue has been utilized and used to help the welfare of the community through various sectors, such as financing infrastructure development projects, helping finance the Education and Health sectors, and helping poverty alleviation programs. These funds come from various sectors such as national resource management, natural resources, and government services. The use of Non-Tax State Revenue (PNBP) funds for the welfare of the people is a strategic step in an inclusive national development effort. However, the use of these funds depends on good management, close supervision, and equitable distribution throughout Indonesia. With proper allocation and transparent management, PNBP funds can be an important tool to improve people's quality of life in various sectors. Paper Type: Descriptive Keywords: Non-Tax State Revenue, Public Welfare, State Budget